Understanding the Impact of an LSAMP Scholar Program - Yang, Lydia Yang; King, Brenee; Betz, Amy R.; Bender, Shana (ASEE, 2023)
In 2020, [a predominately white, midwestern, land grant institution] started a Scholar program as part of their Louis Stokes Alliances for Minority Participation (LSAMP) grant. The goal of this LSAMP grant is to increase the persistence, retention, and graduation rates of underrepresented minority (URM) students. The Scholar program is being piloted at this institution; but if successful, the program may become a model for other institutions within the alliance to implement. The goal of the Scholar program is for students to become more knowledgeable about themselves and what they need to succeed in their academic and personal success. Program description The Scholar program was developed using the theoretical framework of Kamphoff and colleagues’ Empowerment and motivation model (2007). Adapted from this model, the components of the Scholar program focus on four key areas - learning engagement, commitment to learning, awareness of self-management, and self-confidence with campus resources. Specifically, students are required to participate in an online course with modules focused on academic development, interface with campus resources attend scholar chats, and attend academic coaching sessions. Upon completion of the required activities, participants are provided with a stipend. Participants were asked to complete a self-assessment on the abovementioned four areas at the beginning of the Scholar program (pre-test) and after the completion of the program (post-test). Research Question This paper examines whether participants’ pre-test and post-test ratings differ in the following four areas: learning engagement, commitment to learning, awareness of self-management, and self-confidence with campus resources. We hypothesized that the Scholar program makes a difference in participants’ ratings on the pre-test and post-test in all four areas. Recruitment and Participants All current LSAMP recipients were invited to participate in the Scholar program. An email was sent out to eligible students to encourage participation. The invitation email noted a stipend would be provided upon active participation in program activities. Interested students were directed to complete a short application which included open-ended questions related to their cultural background, short- and long-term educational goals and activities in which they are committed. Measures The pre- and post- test questionnaire was developed by modifying from two existing instruments, Michigan State University Student Assets Survey (Livsey, 2003) and the NACADA Academic Advising Survey (2016). The instrument measures the four key areas: learning engagement (9 items), commitment to learning (6 items), awareness of self-management, and self-confidence with campus resources (2 items). Instrument details will be provided in the paper. Results All analyses were conducted using SPSS v27. Data was examined and cleaned first. 57 participants completed both pre-test and post-test and their data were utilized for the following analyses. Dependent samples t-tests were conducted to examine whether participants’ ratings in the pre-test and post-test differ in the four key areas. The preliminary results showed statistically significant increases in participants’ awareness of campus resources (t = 5.759, p < .001) and in knowing how to access campus resources (t = 5.80, p < .001). The final results will be provided in the paper.